Update on the Medical Management of Gastrointestinal Behçet’s Disease - Giuseppe Lopalco; Donato Rigante; Vincenzo Venerito; Claudia Fabiani; Rossella Franceschini; Michele Barone; Giovanni Lapadula; Mauro Galeazzi; Bruno Frediani; Florenzo Iannone; Luca Cantarini (Mediators of Inflammation)
Behçet’s disease (BD) is a multisystemic disorder of unknown etiology mainly defined by recurrent oral aphthosis, genital ulcers, and chronic relapsing bilateral uveitis, all of which represent the “stigmata” of disease. However, many other organs including the vascular, neurological, musculoskeletal, and gastrointestinal systems can be affected. The gastrointestinal involvement in Behçet’s disease (GIBD), along with the neurological and vascular ones, represents the most feared clinical manifestation of BD and shares many symptoms with inflammatory bowel diseases, such as Crohn’s disease and ulcerative colitis. Consequently, the differential diagnosis is often a daunting task, albeit the presence of typical endoscopic and pathologic findings may be a valuable aid to the exact diagnosis. To date, there are no standardized medical treatments for GIBD; therefore therapy should be tailored to the single patient and based on the severity of the clinical features and their complications. This work provides a digest of all current experience and evidence about pharmacological agents suggested by the medical literature as having a potential role for managing the dreadful features of GIBD.